Development of doubled haploid mapping population for drought tolerant high chapati quality Indian wheat variety C306 using wheat x maize system - Grewal, Sapna; Kour, Anupreet; Tiwari, Ratan; Chand, Suresh; Prabhu, K. Vinod; Singh, Nagendra K. (The Indian Journal of Genetics and Plant Breeding, 2017)
Doubled haploid (DH) technology allows production of pure homozygous lines in a single generation. Integration of DH technology in wheat breeding programmes and genetic studies has the potential to reduce the breeding time for new varieties and enhance our understanding of the genetics of important agronomic traits. A protocol was standardized for the production of DH wheat plants using wheat into maize hybridization system and a mapping population of sixty DH wheat lines was produced involvingdrought tolerant high chapati quality Indian wheat varietyC306 and a poor quality variety WH157. Factors were identified for efficient production of DH plants, including early excision of the haploid embryos after pollination, low temperature treatment of the excised embryos and use of lower concentration of colchicine solution for longer time for the chromosome doubling of the haploid plantlets.